The given equation is
![|2x+3|+4=1](https://img.qammunity.org/2023/formulas/mathematics/college/blygqzgknsjx1e6yahcq7c3i7dwetjtas2.png)
First, we need to isolate the absolute value, we'll subtract 4 one each side
![\begin{gathered} |2x+3|+4-4=1-4 \\ |2x+3|=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c2d660m4hmajvjftf2a9mtxvnuhyz82guz.png)
Now, we rewrite the equation in two equations
![\begin{gathered} 2x+3=-3 \\ 2x+3=-(-3)\rightarrow2x+3=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sgc1su5c955kk4ywfbmid7jv2vp2z0rpfq.png)
Let's solve each equation
![\begin{gathered} 2x+3=-3 \\ 2x=-3-3 \\ 2x=-6 \\ x=-(6)/(2)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j3gmtn4ab4cg9glmetbdll6czpkxsidnab.png)
So, the first solution is -3.
![\begin{gathered} 2x+3=3 \\ 2x=3-3=0 \\ x=(0)/(2)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jlrkflldg7usmxds58qhovgdoy2rmnecdj.png)
The second solution is zero.
Therefore, the solutions are -3, and 0.